Gender specific survival rates after deceased donor liver transplantation: A retrospective cohort. (July 2022) - Gabbay, Uri; Issachar, Assaf; Cohen-Naftaly, Michal; Brown, Marius; Nesher, Eviatar
Abstract: Background: According to the literature, there are sex allocation inequalities in liver transplantation (LT). Sex disparities in outcomes after LT have been debated. This study aimed to evaluate sex-specific outcomes after LT, specifically short-term mortality and long-term survival rates. Methods: A retrospective cohort of the entire LT series from to 2010–2019 in a single center in which the inclusion criteria were adults ≥18 YO age who underwent primary deceased donor LT. Mortality rate was evaluated within 30 days and 6 months. Survival rate was evaluated at 1, 3 and 5 years of age. Results: A total of 240 primary and deceased donor LTs (153 men and 87 women) were included. Mean age 55.2Y men and 51.6Y women (p = 0.02). Hepatocellular carcinoma (HCC) was the direct indication in 32.7% of the men and only 17.4% of the women. The leading primary liver morbidities were viral hepatitis (B, C, and D) in 38.3% (N = 92) and nonalcoholic steatohepatitis (NASH) in 20.8% (N = 50) of patients. Thirty-day mortality was 14%, which was significantly higher in men (18%) than in women (8%). Survival rates after 5 years were 64.9% and 78.3%, respectively. Multivariate analysis through logistic regression that included age, direct indication, MELD, and primary liver morbidity revealed statistically significant female to male Odds-Ratio of 0.4 in 30 days, 6 m mortality and a statistically significant higher long-term survival. Conclusions: Our observations revealed better female outcomes, namely, lower short-term mortality and higher long-term survival. Given the consistency after stratification and given the multivariate analysis, this is unlikely to be attributable to confounders. Such findings suggesting consistently better female outcomes have not been previously reported; hence, multi center study is encouraged. Highlights: Gender outcome disparities after liver transplantation (LT) is debated. We present retrospective cohort of 240 consecutive LT in a single center. We found significant lower short-term mortality rates and better long-term survival in women. The outcome disparity was consistent in most underlying liver diseases. We had not identified factors that may confound sex outcome disparity.